2007
DOI: 10.1111/j.1745-3933.2007.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of macroscopic instability and Lyapunov times in the general three-body problem

Abstract: We conducted extensive numerical experiments of equal mass three‐body systems until they became disrupted. The system lifetimes, as a bound triple, and the Lyapunov times show a correlation similar to what has been earlier obtained for small bodies in the Solar system. Numerical integrations of several sets of differently randomized initial conditions produced the same relationship of the instability time and Lyapunov time. Marginal probability densities of the various times in the three‐body experiments are a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 9 publications
3
34
5
Order By: Relevance
“…10). This contrasts with the result in Mikkola & Tanikawa (2007) for the general threebody problem where it was found that a power law with β ≈ 1.8 roughly fits 90 per cent of the data on an interval 0.94 < t l < 35.2. Since the data in Fig.…”
Section: Numerical Resultscontrasting
confidence: 95%
See 4 more Smart Citations
“…10). This contrasts with the result in Mikkola & Tanikawa (2007) for the general threebody problem where it was found that a power law with β ≈ 1.8 roughly fits 90 per cent of the data on an interval 0.94 < t l < 35.2. Since the data in Fig.…”
Section: Numerical Resultscontrasting
confidence: 95%
“…Comparing this plot to fig. 3 in Mikkola & Tanikawa (2007) we note some similarities. First, for small t l the median curve is steeper compared to larger t l values.…”
Section: Sitnikov Problemmentioning
confidence: 63%
See 3 more Smart Citations